2015
DOI: 10.5114/fn.2015.52409
|View full text |Cite
|
Sign up to set email alerts
|

Original article Effect of oral administration of pig spinal cord hydrolysate on clinical and histopathological symptoms of experimental allergic encephalomyelitis in rats

Abstract: A b s t r a c t Oral tolerance is the natural occurring phenomenon of a decreased immune response to previously fed antigens, which prevents induction of a response to dietary antigens. One of the mechanisms is deletion of T lym-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Administration of specific encephalitogenic antigens by various routes, including mucosal, i.v., i.p., s.c. and oral, can induce immune tolerance in EAE [7, 23, 24]. DCs, as professional APCs, can be induced into a tolerogenic phenotype, with the ability to promote the function of regulatory T cells or inhibit activation of autoreactive T cells [2527].…”
Section: Discussionmentioning
confidence: 99%
“…Administration of specific encephalitogenic antigens by various routes, including mucosal, i.v., i.p., s.c. and oral, can induce immune tolerance in EAE [7, 23, 24]. DCs, as professional APCs, can be induced into a tolerogenic phenotype, with the ability to promote the function of regulatory T cells or inhibit activation of autoreactive T cells [2527].…”
Section: Discussionmentioning
confidence: 99%
“…Male Lewis rats were inoculated subcutaneously (sc) in the pad of the left hind paw with 100 μ L antigenic emulsion containing equal volumes of saline with 20 μ g of guinea pig myelin basic protein (MBP) (Sigma-Aldrich, St. Louis, MO) and complete Freund's adjuvant (CFA) (Chondrex, Redmond, WA, USA) with Mycobacterium tuberculosis (2 mg/mL). Daily weight was recorded, and clinical signs were evaluated, using the following 5-grade scale [ 23 ]: 0, no clinical signs; 1, limp tail; 2, hind leg weakness; 3, paraplegia and incontinence; 4, quadriplegia; and 5, moribundity or death.…”
Section: Methodsmentioning
confidence: 99%
“…These data suggest that up-regulation of HO-1 may contribute to diminished neuroprotective benefits of EGCG alone in this EAE model [11]. It has been shown that usage of preparations containing pig spinal cord hydrolysate, as a source of broad spectrum myelin antigens, is able to diminish clinical symptoms of ongoing EAE [13].…”
Section: Real-time Pcrmentioning
confidence: 91%